A cell-based screening system for anti-influenza A virus agents - Wong, W.Y.; Loh, S.W.; Ng, W.L.; Tan, M.C.; Yeo, K.S.; Looi, C.Y.; Maah, M.J.; Ea, C.K. (Nature Publishing Group, 2015)
Emerging of drug resistant influenza A virus (IAV) has been a big challenge for anti-IAV therapy. In this study, we describe a relatively easy and safe cell-based screening system for anti-IAV replication inhibitors using a non-replicative strain of IAV. A nickel (II) complex of polyhydroxybenzaldehyde N4-thiosemicarbazone (NiPT5) was recently found to exhibit anti-inflammatory activity in vivo and in vitro. NiPT5 impedes the signaling cascades that lead to the activation of NF-κB in response to different stimuli, such as LPS and TNFα. Using our cell-based screening system, we report that pretreating cells with NiPT5 protects cells from influenza A virus (IAV) and vesicular stomatitis virus (VSV) infection. Furthermore, NiPT5 inhibits replication of IAV by inhibiting transcription and translation of vRNAs of IAV. Additionally, NiPT5 reduces IAV-induced type I interferon response and cytokines production. Moreover, NiPT5 prevents activation of NF-κB, and IRF3 in response to IAV infection. These results demonstrate that NiPT5 is a potent antiviral agent that inhibits the early phase of IAV replication.